PROGRAM PENGUATAN LEMBAGA DISTRIBUSI PANGAN MASYARAKAT (P-LDPM) TERHADAP KINERJA GAPOKTAN DI KECAMATAN BEKRI KABUPATEN LAMPUNG TENGAH - Agustya Ratna Pratiwi; Serly Silvianti; Rio Tedi Prayitno (Lampung University, 2018)
This research aims to analyze the implementation of the P-LDPM and the difference between the performance of program recipient farmer groups and non-recipient. The research is a survey conducted in Bekri District, Lampung Tengah Region, as Bekri is an area chosen by government as P-LDPM receiver. Respondents are organizers of farmer groups chosen purposively by consideration that the organizers are the people who receive the program directly. The research data are collected in January – February 2018 and analyzed by quantitative descriptive analysis method. The results showed that implementation of the P-LDPM was started in 2013, which known by the donation from government amounted Rp150,000,000.00. The rate of performance of farmer groups recipients of the P-LDPM program was as high categorized. Meanwhile, the rate of performance of farmer groups that do not receive the program was in a medium category. P-LDPM had significant impacts on the rate of performance of farmer groups. Key words: farmer groups combined, performance, P-LDPM